Identifying the components of acidosis in patients with severe plasmodium falciparum malaria Using metabolomics - Leopold, S; Ghose, A; Allman, E; Kingston, H; Hossain, A; Dutta, A; Plewes, K; Chotivanich, K; Day, N; Tarning, J; Winterberg, M; White, N; et al. (Oxford University Press, 2018)
Background Acidosis in severe Plasmodium falciparum malaria is associated with high mortality yet the pathogenesis remains incompletely understood. The aim of this study was to determine the nature and source of metabolic acids contributing to acidosis in patients with severe falciparum malaria. Methods A prospective observational study was conducted to characterise circulating acids in adults with P. falciparum malaria (n=107) and healthy controls (n=45) from Bangladesh using high-resolution LC-MS metabolomics. Additional in vitro P. falciparum culture studies were performed to determine if parasites release the acids detected in plasma from patients with severe malaria acidosis. Results We identified previously unmeasured plasma acids strongly associated with acidosis in severe malaria. Metabolomic analysis of P. falciparum parasites in vitro showed no evidence that these acids are released by the parasite during its life-cycle. Instead ten of the plasma acids could be mapped to a gut microbial origin. Patients with malaria had low L-citrulline levels, a plasma marker indicating reduced gut barrier integrity. Longitudinal data showed the clearance of these newly identified acids was delayed in fatal cases. Discussion These data suggest that a compromise in intestinal barrier function may contribute significantly to the pathogenesis of life-threatening acidosis in severe falciparum malaria.